0419 IL-6 Moderates the Association Between Obstructive Sleep Apnea Severity and Incident Alzheimer's Disease: The Framingham Heart Study. (27th May 2020) - Baril, A; Beiser, A S; Redline, S; McGrath, E R; Aparicio, H J; Gottlieb, D J; Seshadri, S; Himali, J J; Pase, M P
Abstract: Introduction: Both sleep disturbances and inflammation are potential risk factors for Alzheimer's disease (AD). However, it is unknown how inflammation and sleep interact together to influence the risk of developing AD dementia. Our objective was to evaluate whether interleukin-6 (IL-6) levels interact with sleep disturbances when predicting incident clinical AD. Methods: We studied participants in the Framingham Heart Study Offspring cohort who completed in-home overnight polysomnography. Sleep characteristics were continuous and included sleep duration, wake after sleep onset (WASO), and apnea-hypopnea index (AHI). Participants were stratified into quartiles of IL-6 levels. Surveillance for incident AD dementia occurred over a mean follow-up of 13.4±5.4 years. Using Cox proportional hazards regression models, we tested the interaction of sleep measures by IL-6 quartiles on incident AD dementia. All analyses adjusted for age and sex and P<0.05 was considered significant. Results: The final sample included 291 dementia-free participants at baseline (age 67.5±4.9 years, 51.6% men). Approximately one quarter of participants had obstructive sleep apnea (OSA; AHI>15) at baseline (median:6.2, Q1:2, 3, Q3:14.3). We observed 33 cases of incident AD dementia during follow-up. Although no interaction was observed for either sleep duration or WASO with IL-6 levels, there was a significant interaction of AHI with IL-6 in predicting AD dementia (p=0.002). In the lowest IL-6 quartile, higher AHI was associated with an elevated risk of AD dementia (hazard ratio, 4.15 [95%CI, 1.42, 12.1], p=0.01) whereas no association between AHI and incident AD was observed in other IL-6 quartiles. Conclusion: Our findings suggest that the pro-inflammatory cytokine IL-6 moderates the association between OSA and incident AD risk. The association between increasing OSA severity and incident AD was only observed in those with lower IL-6 levels, suggesting that this association might be especially apparent when no other confounding risk factors such as inflammation are present. Support: The Framingham Heart Study is supported by contracts from the National Heart, Lung and Blood Institute, grants from the National Institute on Aging, and grants from the National Institute of Neurological Disorders and Stroke.